Penerapan E-Module Berbasis Problem-Based Learning untuk Meningkatkan Kemampuan Berpikir Kreatif dan Mengurangi Miskonsepsi pada Materi Ekologi Siswa Kelas X MIPA 3 SMA Negeri 6 Surakarta Tahun Pelajaran 2014/2015 - HIDAYATUN, NUNING; KARYANTO, PUGUH; FATMAWATI, UMI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2015)
This research aimed to improve creative thinking ability and to reduce misconception on ecology in the students of X MIPA 3 of SMA Negeri 6 Surakarta in the academic of 2014/2015 through the application of e-module based on Problem-Based Learning. This research was a Classroom Action Research conducted in two cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. The subject of research was the X MIPA 3 graders of SMA Negeri 6 Surakarta in the academic of 2014/2015 consisting of 9 boys and 21 girls. Techniques of collecting data used were essay test to measured creative thinking ability, open ended reasoning of two-tier diagnostic test to measure misconception, observation and interview as the proponent data. The data were analyzed using descriptive qualitative technique consists of three components: data reduction, data presentation, and taking the conclusion. Data validation of this research was triangulation method. Target of the research is an increase 20% on creative thinking aspects and decrease misconception 20% on ecology concepts at the end of the cycle. The result of research showed that there was an increase in each aspect of creative thinking ability: 24.68% of fluency, 34.17% of flexibility, 50% of originality, and 21.67% of elaboration. On the other side, the result of research also showed that there was a decrease in misconception in the important concepts of ecology including: 43.42% of population, 32.78% of community, 20.6% of food chain and web, and 47.92% of the ecology concept in science, environment, technology and community (salingtemas). The conclusion of this research described that the application of e-module based on Problem-Based Learning is able to improve the ability of creative thinking and reduce the students’ misconception in ecology.